THE OLD BELIEVERS OF KULIGA VILLAGE: TRADITIONS AND EVERYDAY LIFE (Philological Studies, 2019)
The article considers the life of the Old Believers and their role in preserving the religious tradition of Verkhokamye. The authors describe the modern structure of the Kuliginskaya community and prove that the central place in it is occupied by the confessor and the scribe who organize the ritual space. The study is based on the results of field work carried out in last few years
Keywords: Verkhokamye; Old Believers; bespopovstvo; tradition; diary